2012
DOI: 10.1002/eji.201142274
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the ST2 proximal promoter disrupts fibroblast‐specific expression but does not reduce the amount of soluble ST2 in circulation

Abstract: IL-33 signals through ST2, which is expressed either as a full-length signaling receptor or a truncated soluble receptor that can suppress IL-33 activity. Previous data suggest that soluble ST2 mRNA in fibroblasts is coupled to a serum-inducible proximal promoter, while full-length ST2 expression in immune cells is directed from a distal promoter. In order to better understand the function of the alternative promoters and how they ultimately affect the regulation of IL-33, we generated a mouse in which the ST2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…A recent study showed that deletion of the proximal ST2 promoter disrupts fibroblast-specific sST2 expression but does not affect serum sST2 levels (43). These results may be reconciled with our findings by considering that ST2 promoter usage appears to be highly cell-type dependent and that fibroblasts may not be the major source of circulating sST2.…”
Section: Discussionsupporting
confidence: 81%
“…A recent study showed that deletion of the proximal ST2 promoter disrupts fibroblast-specific sST2 expression but does not affect serum sST2 levels (43). These results may be reconciled with our findings by considering that ST2 promoter usage appears to be highly cell-type dependent and that fibroblasts may not be the major source of circulating sST2.…”
Section: Discussionsupporting
confidence: 81%
“…It was first suggested that the expression of the two ST2 variants was controlled at the transcriptional level, with sST2 expressed from the proximal promoter in fibroblasts and ST2L from the distal promoter in hematopoietic cells [79]. However, more recent data indicate that, although ST2 promoter usage is indeed largely cell-type dependent, it does not dictate splicing, so that both ST2L and sST2 can be expressed from the same promoter [82,83]. Soluble sST2 protein is found in the circulation, where it can reach concentrations in the ng/mL range, but the cellular sources of circulating sST2 are still unknown.…”
Section: Sst2mentioning
confidence: 98%
“…For example, while both the human leukaemic cell line, UT-7 and mast cells can transcribe ST2 isotypes using either the distal or proximal promoter, the distal promoter is predominantly used in this cell line for expression of both sST2 and ST2L [20]. Conversely, almost all transcription is initiated from the proximal promoter in fibroblasts [21]. Unlike other IL-1 family members, there is no known antagonistic ligand for ST2.…”
Section: (Figure1)mentioning
confidence: 99%